Swell Generation Under Extra‐Tropical Storms. Issue 9 (27th September 2021) - Hell, M. C.; Ayet, Alex; Chapron, Bertrand
Abstract: Storms propagate over the ocean and create moving patches of strong winds that generate swell systems. Here, we describe the dynamics of wave generation under a moving storm by using a simple parametric model of wave development, forced by a temporally and spatially varying moving wind field. This framework reveals how surface winds under moving storms determine the origin and amplitude of swell events. Swell systems are expected to originate from locations different than the moving high‐wind forcing regions. This is confirmed by a physically informed optimization method that back‐triangulates the common source locations of swell using their dispersion slopes, simultaneously measured at five wave‐buoy locations. Hence, the parametric moving fetch model forced with reanalysis winds can predict the displacement between the highest winds and the observed swell source area. The model further shows that the storm's peak wind speed is the key factor determining swell energy since it determines surface wind gradients that lead to the spatial convergence of wave energy into a much smaller area than the wind fetch. Swell generation can then be described to follow a three‐stage process that outlines a focus area where swell energy is enhanced and slightly displaced from the maximum wind locations. This analysis provides an improved understanding of fetches for extra‐tropical swell systems and may help to identify biases in swell forecast models, air‐sea fluxes, and upper‐ocean mixing estimations. Plain Language Summary: Storms generate waves on the ocean surface that can travel across entire ocean basins, the so‐called swell waves. However, it is unclear how the amplitude and period of these surface waves depend on the strength and shape of the storm. One has to consider the movement of the storm in addition to its size, lifetime, and wind speeds. This study shows how all these parameters control the amplitude and period of swell events reaching the coastlines. We find that the storm's movement and its peak wind speed compress the wave energy to a small area, which then appears as a swell source location in the open ocean. This study can help to improve swell forecasts and understand how long‐term changes in mid‐latitude storms would modify the exchange of momentum and heat between the atmosphere and the ocean. Key Points: Wave generation by a moving extra‐tropical storm is described using a Gaussian wind field and a parametric model of wave development A new developed machine‐learning algorithm triangulates the space‐time evolving source point of swell systems from buoy measurements This model describes the distance between swell source and the storm's maximum wind speed and reveals sensitivities to storm's parameters